Ameloblastic fibro-odontoma: A diagnostic challenge - Abhijeet Alok; Indra Deo Singh; Shivani Singh (Wolters Kluwer Medknow Publications, 2015)
Ameloblastic fibro-odontoma (AFO) is a rare mixed odontogenic tumor. It occurs predominantly in children and young adults with no sex predilection, mostly in the mandible posterior region. A painless swelling is the most common clinical sign of AFO. Radiographically, AFO shows a circumscribed radiolucency, which contains radiopaque foci of various sizes and shapes. Histological examination reveals a fibrous soft tissue, islands of odontogenic epithelium, and a disordered mixture of dental tissues. Treatment of AFOs usually consists of enucleation or surgical curettage, which is possible due to their benign biological behavior. Here, we are reporting a case of AFO in a 20-year-old male.